Is the Salut Programme an effective and cost-effective universal health promotion intervention for parents and their children? A register-based retrospective observational study. Issue 9 (21st September 2017) - Häggström, Jenny; Sampaio, Filipa; Eurenius, Eva; Pulkki-Brännström, Anni-Maria; Ivarsson, Anneli; Lindkvist, Marie; Feldman, Inna
Abstract : Objectives: This study investigates the effectiveness and cost-effectiveness of the Salut Programme, a universal health promotion intervention, compared with care-as-usual, over the periods of pregnancy, delivery and the child's first 2 years of life. Method: We adopted a register-based retrospective observational design using existing data sources with respect to both exposures and outcomes. Health outcomes and costs were compared between geographical areas that received care-as-usual (non-Salut area) and areas where the programme was implemented (Salut area). We included mothers and their children from both the Salut and non-Salut areas if: (1) the child was born 2002–2004 (premeasure period) or (2) the child was born 2006–2008 (postmeasure period). The effectiveness study adopted two strategies: (1) a matched difference-in-difference analysis using data from all participants and (2) a longitudinal analysis restricted to mothers who had given birth twice, that is, both in the premeasure and postmeasure periods. The economic evaluation was performed from a healthcare and a limited societal perspective. Outcomes were clustered during pregnancy, delivery and birth and the child's first 2 years. Results: Difference-in-difference analyses did not yield any significant effect on the outcomes. Longitudinal analyses resulted in significant positive improvement in Apgar scores, reflecting the newborn's physical condition, with more children having a normal Apgar score (1 min +3%, 5 min +1%). The cost of the programme was international dollar (INT$)308/child. From both costing perspectives, the programme yielded higher effects and lower costs than care-as-usual, being thus cost-saving (probability of around 50%). Conclusions: Our findings suggest that the Salut Programme is an effective universal intervention to improve maternal and child health, and it may be good value for money; however, there is large uncertainty around the cost estimates.